Evaluation of Juveniles Pushed to Crime: A Retrospective Study - Erdem Hösükler; Aziz Yılmaz; Zehra Zerrin Erkol (Adli Tıp Bülteni, 2022)

(untitled)
Objective:Evaluation of children and adolescents pushed to crime should be different from adult offenders. In this study, it is aimed to analyze the qualities of children and adolescents pushed to crime and to discuss them in the light of the literature.Methods:Children who were evaluated in terms of criminal liability at Bolu Abant İzzet Baysal University Faculty of Medicine Department of Forensic Medicine and Bolu Forensic Medicine Branch Office between January 1, 2016 and December 31, 2018 were included in the study.Results:A total of 237 children and adolescents were included in the study. Of the cases, 76.8% (n=182) were male and 23.2% (n=55) were female. The mean age was 13.38±0.83. Of the cases, 80.6% were living in the nuclear family. Twenty-two cases (9.3%) were working in any job and sixty-four (27%) of the cases had one or more substance use history. Of the cases, 47.7% committed deliberate wounding crimes whereas 20.3% of cases committed burglary crimes. One hundred and fifty two cases (64.1%) committed a crime for the first time. One hundred and ten (46.4%) cases committed the crime together with a group of friends. Forty-seven cases (19.8%) had a psychiatric disorder. In 60.8% of the cases (n=144), it was reported that they had criminal responsibility.Conclusion:It is necessary to increase the number of child support centers and to develop effective intervention methods for juveniles pushed to crime in these centers, and more studies should be conducted on these issues.